2022
DOI: 10.3897/zookeys.1084.71576
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitogenomes of four Trichiurus species: A taxonomic review of the T. lepturus species complex

Abstract: Four Trichiurus species, T. japonicus, T. lepturus, T. nanhaiensis, and T. brevis, from the coasts of the China Seas, have been identified and their entire mitochondrial genomes (mitogenomes) have been sequenced by next-generation sequencing technology. A comparative analysis of five mitogenomes was conducted, including the mitogenome of T. gangeticus. The mitogenomes contained 16.568–16.840 bp and encoded 36 typical mitochondrial genes (13 protein-coding, 2 ribosomal RNA-coding, and 21 transfer RNA-coding gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Two species groups were recognized: the T. lepturus complex, which has an anal opening positioned vertically at the 38th to 41st dorsal fin rays, and the T. russelli complex, which has an anal opening positioned vertically at the 34th to 35th dorsal fin rays (Table 2) (Burhanuddin et al, 2002). Within the T. lepturus complex, T. japonicus has a longer tail, and T. lepturus has a whitish dorsal fin when fresh; in contrast, T. nanhaiensis has a yellowish-green dorsal fin (Hsu et al, 2009); the frontal bone of T. nanhaiensis is very smooth, the frontal bone of T. japonicus is slightly inverted, and the frontal bone of T. lepturus is obviously inverted and bulges in the upper part of the orbit and is accompanied by indentation (Figures S1, S2; Yi et al, 2022). A total of 1,551 bp of the COI gene was sequenced.…”
Section: Species Identificationmentioning
confidence: 99%
“…Two species groups were recognized: the T. lepturus complex, which has an anal opening positioned vertically at the 38th to 41st dorsal fin rays, and the T. russelli complex, which has an anal opening positioned vertically at the 34th to 35th dorsal fin rays (Table 2) (Burhanuddin et al, 2002). Within the T. lepturus complex, T. japonicus has a longer tail, and T. lepturus has a whitish dorsal fin when fresh; in contrast, T. nanhaiensis has a yellowish-green dorsal fin (Hsu et al, 2009); the frontal bone of T. nanhaiensis is very smooth, the frontal bone of T. japonicus is slightly inverted, and the frontal bone of T. lepturus is obviously inverted and bulges in the upper part of the orbit and is accompanied by indentation (Figures S1, S2; Yi et al, 2022). A total of 1,551 bp of the COI gene was sequenced.…”
Section: Species Identificationmentioning
confidence: 99%
“…The analysis of whole mitogenomes is attractive since they represent a compromise between single markers and whole genome analysis. The conserved properties of animal mitogenomes, the advantage of using multigene datasets, and the continued ease of acquisition would provide a promising strategy for species identification and population genetics using whole mitogenomes [21]. Whole mitogenomes were successfully used to determine the population structure of the Chinese seabass (Lateolabrax maculatus) in China [22] and Mansonia mosquitoes in Brazil [23].…”
Section: Introductionmentioning
confidence: 99%
“…Trichiurus species play a significant role in commercial marine fisheries (FAO, 2004); however, their systematic classification remains unresolved due to the considerable resemblance among species within the genus, particularly in terms of physical appearance and silvery colouration (Yi et al, 2022). According to Eschmeyer's Catalog of Fishes (ECoF, Fricke et al, 2021), valid Trichiurus species are categorized into two complexes: the Trichiurus lepturus complex, often denoted as the large‐headed or long‐tailed species complex, and the Trichiurus russelli complex, known as the short‐tailed species complex (Burhanuddin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The largehead hairtail, T. lepturus Linnaeus, 1758, has been registered as a cosmopolitan species exhibiting a broad global distribution and significant commercial value as a fishery resource on a global scale (Froese & Pauly, 2021; Martins et al, 2005). However, recent studies have reported that some published papers have misidentified this species in the Indian and Pacific oceans (Burhanuddin & Parin; Chakraborty & Iwatsuki, 2006; 2008; Yi et al, 2022). Its capture extends across a substantial portion of its habitat, encompassing both inshore and offshore waters.…”
Section: Introductionmentioning
confidence: 99%